Pengaruh Program Sertifikasi Halal terhadap Penjualan Produk Umkm Bidang Pangan di Kabupaten Gresik - Nila, Nila Salsabila Aufa; Kambali, Muhammad; Permanasari, Lukita (Al-Maqashid: Journal of Economics and Islamic Business, 2024)
This study aims to determine the effect of the halal certification program on the sales of MSMEs in the food sector in Gresik Regency. The halal certification program itself is a form of government effort to protect its citizens who are predominantly Muslim from food and drinks that are forbidden by God for consumption by Muslims. The halal certification program is mandatory for MSME actors, especially in the food sector, including in Gresik Regency. The research method uses a quantitative approach. The population in this study were MSME actors in the food sector who had been halal certified in Gresik Regency. While the sample in this study was determined by the slovin method from the population. The problems that are sought to be answered through this study are: a) How is the halal certification program for MSME products in the food sector in Gresik Regency? b) How are the sales of MSME products in the food sector in Gresik Regency? and c) Is there an effect of the halal certification program on the sales of MSME products in the food sector in Gresik Regency? Data were collected through distributing questionnaires using the non-probability sampling technique, purposive technique. The results of the study showed that the halal certification program had an effect on product sales.